ANALISIS PERMINTAAN DAN PENAWARAN UANG DI INDONESIA - Isra Hayati (Quantitative Economics Journal, 2013)
Demand and supply of money plays an important role in monetary policy in every economy. In a closed economy, the demand and supply of money is influenced by the behavior of banks and the public. Being in an open economy, influenced by the amount of income, the ratio of trade through the influence of interest rates and increasing trend in the general price level continuously over time from a country.This study aims to see the effect of real income, interest rate, reserve requirement and the minimum level of consumer prices to the demand and supply of money in Indonesia.Processing of data using quantitative data and descriptive empirical models of money demand is a function of real income, interest rates and general price level. While the empirical model of the money supply is a function of high-powered money. This study examines the mechanisms and magnitude of the effect of real income, interest rates, general price levels, statutory minimum, and the stock of money in a broad sense over the period 1990 to 2010.By using simultaneous equations Two-Stage Least Square (2SLS), suggesting that the effect of general price level has positive and significant, real income is positive but not significant effect, the interest rate a negative and significant effect on the demand and supply of money in Indonesia. Meanwhile, the stock of money in the importance and the general price level has positive and significant, and the statutory minimum level of real income a negative and no significant effect on interest rates.